Peran Pendidikan Anak Pada Perubahan Stratifikasi Sosial Masyarakat Di Jorong Pasar Usang Guguk Kecamatan Gunung Talang Kabupaten Solok. - Oktavia, Nita - (Pendidikan Sosiologi, 2014)
The background of this research by the basic assumptions about the role of childrenâs education on changes in sosial stratification in Jorong Pasar Usang Guguk Kecamatan Gunung Talang Kabupaten Solok. Associated with the reality on the ground that education greatly affects the position of the ellipse pairs of worn Guguk society especially those who come from poor families. Therefore, the problem can be formulated as follows: how to change the role of the education of children in the social stratification of society in Jorong Pasar Usang Guguk Kecamatan Gunung Talang Kabupaten Solok. This study aimed to describe the role of childrenâs education in social stratification changes in Jorong Pasar Usang Guguk Kecamatan Gunung Talang Kabupaten Solok education post.Theories have used in this study is structural functionalism (Robert K. Merton). Type of study is a qualitative research and descriptive. Informants in this study is community Jorong Pasar Usang Guguk underprivileged who have education. The selection of informants using purposive sampling. Informants in the study of eight people, with the type of primary and secondary data. Data collection methods used were observation, interviews, and documentation. Data analysis starts from a data reduction, data display, and conclusion.The results of this study concluded that, the role of childrenâs education on changes in sosial stratification in Jorong Pasar Usang Guguk Kecamatan Gunung Talang Kabupaten Solok is 1) improve the family economy, 2) the growing importance of education for the local community, 3) received an award from the community.